2021
DOI: 10.21203/rs.3.rs-877642/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Study of Silicon Nitride Waveguide Platform for On-Chip Virus Detection: Prospects for COVID-19

Abstract: This work presents a rigorous sensitivity analysis of silicon nitride on silicon dioxide strip waveguide for virus detection, focusing on COVID-19. In general, by functionalizing the waveguide surface with specific antibodies layer, we make the optical sensor sensitive only to a particular virus. Unlike conventional virus detection methods such as polymerase chain reaction (PCR), integrated refractive index (RI) optical sensors offer cheap and mass-scale fabrication of compact devices for fast and straightforw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…RS. El Shami et al proposed a Si 3 N 4 strip waveguide to be used for virus detection with high sensitivity and selectivity and determined optimal dimensions and wavelength to maximize the sensitivity [113]. In another work, P. Xiao et al reported a method using a symmetrical metal-cladding waveguide technology to detect surface antigen of HBV (HBsAg).…”
Section: Optical Waveguide-based Virus Detectionmentioning
confidence: 99%
“…RS. El Shami et al proposed a Si 3 N 4 strip waveguide to be used for virus detection with high sensitivity and selectivity and determined optimal dimensions and wavelength to maximize the sensitivity [113]. In another work, P. Xiao et al reported a method using a symmetrical metal-cladding waveguide technology to detect surface antigen of HBV (HBsAg).…”
Section: Optical Waveguide-based Virus Detectionmentioning
confidence: 99%